Crp Is a Global Regulator of Antibiotic Production in Streptomyces - Chan Gao (American Society for Microbiology, 2012)
ABSTRACT Cyclic AMP receptor protein (Crp) is a transcription regulator controlling diverse cellular processes in many bacteria. In Streptomyces coelicolor, it is well established that Crp plays a critical role in spore germination and colony development. Here, we demonstrate that Crp is a key regulator of secondary metabolism and antibiotic production in S. coelicolor and show that it may additionally coordinate precursor flux from primary to secondary metabolism. We found that crp deletion adversely affected the synthesis of three well-characterized antibiotics in S. coelicolor: actinorhodin (Act), undecylprodigiosin (Red), and calcium-dependent antibiotic (CDA). Using chromatin immunoprecipitation-microarray (ChIP-chip) assays, we determined that eight (out of 22) secondary metabolic clusters encoded by S. coelicolor contained Crp-associated sites. We followed the effect of Crp induction using transcription profiling analyses and found secondary metabolic genes to be significantly affected: included in this Crp-dependent group were genes from six of the clusters identified in the ChIP-chip experiments. Overexpressing Crp in a panel of Streptomyces species led to enhanced antibiotic synthesis and new metabolite production, suggesting that Crp control over secondary metabolism is broadly conserved in the streptomycetes and that Crp overexpression could serve as a powerful tool for unlocking the chemical potential of these organisms. IMPORTANCE Streptomyces produces a remarkably diverse array of secondary metabolites, including many antibiotics. In recent years, genome sequencing has revealed that these products represent only a small proportion of the total secondary metabolite potential of Streptomyces. There is, therefore, considerable interest in discovering ways to stimulate the production of new metabolites. Here, we show that Crp (the classical regulator of carbon catabolite repression in Escherichia coli) is a master regulator of secondary metabolism in Streptomyces. It binds to eight of 22 secondary metabolic gene clusters in the Streptomyces coelicolor genome and directly affects the expression of six of these. Deletion of crp in S. coelicolor leads to dramatic reductions in antibiotic levels, while Crp overexpression enhances antibiotic production. We find that the antibiotic-stimulatory capacity of Crp extends to other streptomycetes, where its overexpression activates the production of “cryptic” metabolites that are not otherwise seen in the corresponding wild-type strain.